642 Work related musculoskeletal disorders among orthopaedic surgeons: a survey study. (24th April 2018) - Sharan, Deepak; Rajkumar, Joshua Samuel; Balakrishnan, Rajarajeshwari
Abstract : Introduction: Surgeons, especially Orthopaedic Surgeons (OS) maintain awkward postures and repetitive tasks which are ergonomically risky. However, there is a paucity of data on the prevalence of work related musculoskeletal disorders (WRMSD) among OS. Hence, the objective was to evaluate the prevalence and risk factors of WRMSD among OS. Methods: A survey was conducted using a structured questionnaire, disseminated online. There were 57 respondents, who were OS with a minimum working experience of one year, and the surgeons were practicing in the field of orthopaedics only. The structured questionnaire included demographic details such as age, sex, height, weight, total work experience, number of working hours in a day, type or department of work, questions related to regular exercise, physical risk factors associated with working condition, present health status. Nordic Musculoskeletal Questionnaire (NMQ) was used to know the regional involvement, prevalence and disability rate of MSD, in past 7 days or during the last 12 months. The short form of work style questionnaire was used to assess the risk factors of adverse work style. Data were recorded and analysed. Result: The mean age of the OSs was 46.32 years and were predominantly males (96%). On an average, the percentage of OSs with operating hours more than 14 hours was 75.4%. Joint replacement (50.9%) and Arthroscopic surgeries (35.1%), were the commonest surgical procedures carried out by them. A high prevalence rate of work related musculoskeletal symptoms among OS was found, mainly in the low back (68.42%), neck (56.14%), shoulder (42.1%) and upper back (31.57%) regions. Sustained static and/or awkward posture was perceived as the factor most commonly associated with low back and neck symptoms by 84.2% of respondents. Discussion: A high prevalence of musculoskeletal symptoms was reported among OS and interventions to address the risk factors identified are recommended.